Noninvasive ventilation in patients with acute cardiogenic pulmonary edema - Andrea Bellone; Massimiliano Etteri; Luca Motta; Anna Cappelletti; Chiara Morichetti; Paolo Pina; Roberto Pusinelli; Massimo Guanziroli (Emergency Care Journal, 2013)
The term noninvasive ventilation (NIV) encompasses two different modes of delivering positive airway pressure, namely continuous positive airway pressure (CPAP) and bilevel positive airway pressure (bilevel-PAP). The two modes are different since CPAP does not actively assist inspiration whereas bilevel-PAP does. Bilevel-PAP is a type of noninvasive ventilation that helps keep the upper airways of the lungs open by providing a flow of air delivered through a face mask. The air is pressurized by a machine, which delivers it to the face mask through long, plastic hosing. With bilevel-PAP, the doctor prescribes specific alternating pressures: a higher pressure is used to breathe in (inspiratory positive airway pressure) and a lower pressure is used to breath out (expiratory positive airway pressure). Noninvasive ventilation has been shown to reduce the rate of tracheal intubation. The main indications are exacerbation of chronic obstructive pulmonary disease and acute cardiogenic pulmonary edema (ACPE). This last is a common cause of respiratory failure with high incidence and high mortality rate. Clinical findings of ACPE are related to the increased extra-vascular water in the lungs and the resulting reduced lung compliance, increased airway resistance and elevated inspiratory muscle load which generates a depression in pleural pressure. These large pleural pressure swings are responsible for hemodynamic changes by increasing left ventricular afterload, myocardial transmural pressure, and venous return. These alterations can be detrimental to patients with left ventricular systolic dysfunction. Under these circumstances, NIV, either by CPAP or bilevel-PAP, improves vital signs, gas exchange, respiratory mechanics and hemodynamics by reducing left ventricular afterload and preload. In the first randomized study which compared the effectiveness of CPAP plus medical treatment vs medical treatment alone, the CPAP group showed a significant decrease in its 48 h mortality rate and no patient required endotracheal intubation. This result was successively confirmed in many reviews and meta-analyses. There are still unanswered questions regarding the role of NIV in ACPE: this review aims to support clinicians treating patients in emergency departments with various presentations of ACPE. It also covers recent developments in the treatment of ACPE and associated evidence.